PHYSICS IN DIGITAL GAMES - Pastori Noveli, Leonardo; de Lucca Filho, João (Revista Interface Tecnológica, 2024)
Explore and elaborate concepts on how real-world physics principles can be applied to the development of digital games, providing greater realism and immersion. The research aims to describe and present simple and effective methods for applying the laws of physics in game development environments through examples and basic techniques. The study demonstrates how simulations of physical phenomena such as gravity, collisions and movements can be developed in a practical way using Newtonian physics as an example and methods developed by the author himself. The results demonstrate the relevance of physics in game design, showing that the use of physics increases the quality of the players' experience, making it more immersive and dynamic. Therefore, the appropriate use of physics is essential to achieve more realism and immersion in games with greater depth.
Keywords: Development of digital games; Digital Games; Games; Video Game; Physics